PERKEMBANGAN REGULASI PERTAMBANGAN DAN EFEKTIVITASNYA DALAM PENGAWASAN LINGKUNGAN DI INDONESIA - Nugroho Dwi Jatmoko; Agustinus Nopi (Jurnal Salome : Multidisipliner Keilmuan, 2025)
This study aims to analyze the role of mining law regulations in environmental compliance enforcement in Indonesia through a systematic literature review. Although Indonesia has a relatively comprehensive regulatory framework covering licensing, EIA, reclamation, and post-mining, studies have shown that the effectiveness of these rules has not been fully reflected in practice. Inconsistency in implementation, weak supervisory capacity, and overlapping authority between levels of government are the main factors that hinder the success of environmental compliance enforcement. In addition, the compliance of mining companies is affected by a combination of regulatory and non-regulatory factors, including market pressures, international standards, and community participation. The results of the thematic analysis show that the issue of implementation is more dominant than the issue of regulatory substance. This research emphasizes the need to strengthen institutional capacity, harmonize regional central governance, and use of supervision technology as a strategic effort to increase the effectiveness of regulations and realize sustainable mining governance.